Variable Waist-Diameter Mach–Zehnder Tapered-Fiber Interferometer as Humidity and Temperature Sensor - Soltanian, M.R.K.; Sharbirin, A.S.; Ariannejad, M.M.; Amiri, I.S.; De La Rue, R.M.; Brambilla, G.; Rahman, B.M.A.; Grattan, K.T.V.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2016)
In-line single-mode tapered-fiber Mach-Zehnder interferometer (MZI-SMTF) with average waist diameters (davg) of 4.05 and 2.89 μ m have been fabricated, and both the temperature and the humidity sensitivity of the surrounding media have been measured and compared. The humidity and the temperature were measured over the ranges from 0% to 90% and 28 °C to 40 °C, respectively. The stability of the system at 50%RH and 90%RH was investigated, while the temperature of the chamber was maintained at about 28 °C. The humidity and temperature sensitivity resolution values were 0.02 nm/%RH and 0.05 nm/0.1 °C for the MZI-SMTF-1 with an average waist diameter of 4.05 μ m , while they were 0.01 nm/%RH and 0.025 nm/0.1 °C for the MZI-SMTF-2 with an average waist diameter of 2.89 μ m.